A Simple Microsoft Excel Method to Predict Antibiotic Outbreaks and Underutilization. (3rd May 2017) - Miglis, Cristina; Rhodes, Nathaniel J.; Avedissian, Sean N.; Zembower, Teresa R.; Postelnick, Michael; Wunderink, Richard G.; Sutton, Sarah H.; Scheetz, Marc H.
Abstract : Benchmarking strategies are needed to promote the appropriate use of antibiotics. We have adapted a simple regressive method in Microsoft Excel that is easily implementable and creates predictive indices. This method trends consumption over time and can identify periods of over- and underuse at the hospital level. Infect Control Hosp Epidemiol 2017;38:860–862